Discussing the stabilizing bacteriorhodopsin through spin coating method in protein nano-memory - Molai Rad, Ahmad; Nazarian, Niloofar; Leilabadi asl, Amineh; Pooladi, Mehdi (Archives of Advances in Biosciences, 2013)
Protein memories are novel technologies which use the hidden abilities of bacteria proteins and biological molecules in order to the electronic processes. Four decades before baceriorhdopsin ( BR) protein was extracted from the membrane of Halobacerinum Salina rum found in high salt water depositions after its original discovery in 1967. In this study, for immobilizing the protein a film has been provided from the different weight/volume use of polyvinyl alcohol and gelatin polymers. Then a suspension of protein bacteriorhodopsin with the 3/2 mg.ml -1 has been used that according to the spectroscopy and determining their activity, optimizing concentration of a film containing bacteriodospian has been obtained. Polymeric film containing bacteriorhodopsin protein has been injected on the glass and by use of spin coater, after obtaining optimizing protocol become stabilized. After that the biological activity of the bacteriorhodopsin protein has been studied. Several biological molecules are being considered based on their usage in computers sciences, as though the bacterial protein – BR has generated much interest among scientists. Functional immobilization of membrane proteins requires consideration of their physiological needs, often dictated by the quality and components of the natural hydrophobic environment surrounding this class of proteins.